2021
DOI: 10.3390/ph14090940
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Anti-Inflammatory Potential of Thymoquinone and Lycopene Mitigate the Chlorpyrifos-Induced Toxic Neuropathy

Abstract: CPF (chlorpyrifos) is an organophosphate pesticide used in agricultural and veterinary applications. Our experiment aimed to explore the effects of thymoquinone (TQ) and/or lycopene (LP) against CPF-induced neurotoxicity. Wistar rats were categorized into seven groups: first group served as a control (corn oil only); second group, TQ (10 mg/kg); third group, LP (10 mg/kg); fourth group, CPF (10 mg/kg) and deemed as CPF toxic control; fifth group, TQ + CPF; sixth group, (LP + CPF); and seventh group, (TQ + LP +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 51 publications
3
26
0
Order By: Relevance
“…Consequently, progressive accumulation of sloughed epithelia in the tubular lumen might explain the dilated tubules in the DLM-injured group [ 43 ]. It is strongly reported that inflammatory response is associated with oxidative stress; herein, the inflammatory cell infiltrations were seen in the liver and kidney tissue after DLM exposure [ 40 , 45 ]. All of these observed pathological lesions were improved after supplementation of NAC.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Consequently, progressive accumulation of sloughed epithelia in the tubular lumen might explain the dilated tubules in the DLM-injured group [ 43 ]. It is strongly reported that inflammatory response is associated with oxidative stress; herein, the inflammatory cell infiltrations were seen in the liver and kidney tissue after DLM exposure [ 40 , 45 ]. All of these observed pathological lesions were improved after supplementation of NAC.…”
Section: Discussionmentioning
confidence: 97%
“…Accumulative evidence suggested that a large amount of hydroxyl radical (OH • ) are produced during oxidative stress. OH • is the most injurious radical compared to other ROS that has a great affinity to the lipid content of the cell membrane [ 34 , 39 , 40 , 41 , 42 , 43 ]. Therefore, it is strongly suggested that the increased MDA levels was associated with DLM-induced ROS production.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations